PRODUKSI BIODIESEL KASAR DARI BEKATUL DENGAN METODE ESTERILIKASI IN SITU - Puspitojati, Endah (Jurnal Ilmu-Ilmu Pertanian, 2009)
Biodiesel is a promising alternative fuel that can be produced From vegetable oils, animal fats or recycled frying oil by esterification or transesterification with alcohol. Rice bran is one of an alternative feedstock to produce biodiesel. The aims of this research are to produce crude biodiesel by in situ esterification without incubation and incubation of rice bran at lipase optimum temperature and pH using sulfuric acid as catalyst, and to characterize rice bran biodiesel by analyzing concentration of fatty acid methyl ester (FAME), triglyceride, diglyceride and monoglyceride, biodiesel yield, density, viscosity, cetane index, cloud point and flash point. The research used in situ esterification. The extraction and biodiesel production occurred simultaneously. Rice bran was incubated at optimum temperature and pH before in situ esterification for one, two and three weeks incubation. Rice bran lipase had the highest activity of 7.89 pmol/ml minute at 33C and pH 6. 50 gram rice bran was transferred to three round bottom flask and 200 ml methanol was added. The mixtures was refluxed with 5 ml catalyst of sulfuric acid for 60, 90 and 120 minutes. During incubation, there was significant increase of fatty acids concentration From 10,34 to 80,74 % then followed by decreasing triglyceride from 89,66 to 19,26 %. Rice bran had the fat content of 19,84-20,81 %. The yield of crude biodiesel was 18,25 to 22,12 %. There was significant decrease in fatty acid concentration of rice bran residual oil. Rice bran crude biodiesel had the density of 852,45 kg/m- 896,72 kg/m; certain index of 32,5 - 53 ;flash point of 70,50 - 79,62 C ; cloud point of 3,5 15 C ; viscosity of 1,12-1,69 Cst. The best treatment was rice bran crude biodiesel at three weeks incubation of rice bran and 60 minutes of esterification. It had the following t:haructtri:ttic's ; FAME percentation of 94,57 %; kinematic viscosity of 1,69 Cst; density of 852,45 km/m; flash point of 79,67 C ; cetane index of 53 : and cloud point of 10C